Hubungan Habits of Mind Matematis dengan Higher Order Thinking Skills Siswa - Niswah, Dina Noor Fa’izatun; Malasari, Putri Nur (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2024)
Mathematics learning facilitates students to have the ability to think, analyse and solve problems critically and creatively. However, most students still struggle and give up easily in solving mathematics problems that require more reasoning. This indicates that students' mathematical habits of mind (HoM) and higher order thinking skills (HOTS) are not optimal. Therefore, this study aims to prove whether there is a relationship between mathematical HoM and HOTS of madrasah tsanawiyah students and how much mathematical HoM contributes to students' HOTS. This correlational research used a quantitative approach. The study population involved all ninth-grade students of MTs Ma'ahid Kudus, while the sample was 72 students selected using simple random sampling technique. Data were obtained through habit of mind questionnaire and higher order thinking skills test. The findings of the research results are (1) there is a significant relationship between mathematical HoM and HOTS of madrasah tsanawiyah students. This can be seen from the Spearman rank correlation coefficient of 0.371 with a sig value. 0.001 0.05; and (2) mathematical HoM contributes 13.76% to students' HOTS. Mathematical HoM that is trained continuously will shape smart thinking and behaviour that can support the improvement of students' HOTS.